Elastic-plastic Contact Analysis of the Planetary Roller Screw Mechanism - Yao Qin; Wu Liyan; Liu Geng; Ma Shangjun; Tong Ruiting (Jixie chuandong, 2016)
Aiming at elastic- plastic contact of planetary roller screw mechanism（ PRSM）,a single contact model between screw and roller is established based on the Hertz contact theory and elastic- plastic mechanics,then a method for judging whether the PRSM has entered the yield state is obtained. Secondly,the numerical model of the elastic- plastic contact is built based on the finite element method and the relationship between loads and deformation on the elastic- plastic contact of PRSM is analyzed. Conclusions can be drawn that the roller becomes a yield state prior to the screw through further analysis,and the contact stress calculation method based on the Hertz contact theory is still feasible when the load is under a range of small plastic deformation. Through the elastic- plastic contact analysis of PRSM,its plastic deformation corresponding to static load rating is acquired,which provides theoretical roles for future design of PRSM.